Analisis Parameter Iklim di Wilayah Pesisir dan Pegunungan Papua Berdasarkan Fenomena ENSO dan IOD - Fuadi, Helmi; Wahyujati, Huda; Rohmah, Irgi Asy Syifa; Saputra, Muhammad Ahnaf Hilman (PT. Pubsains Nur Cendekia, 2026)
Climate change is a global issue that affects many aspects of life, including rainfall and temperature patterns, which are often influenced by the El Niño-Southern Oscillation (ENSO) phenomenon. Papua, with its varied geographical and topographic characteristics, makes it an appropriate region for studying climate variability between coastal and mountainous areas. This study aims to understand climate variability in Papua by analysing differences in rainfall, temperature, humidity, and wind patterns between the two regions in the period 2007 to 2020. The method used in this study is comparative descriptive analysis, using data from the Wamena Meteorological Station and the Dok II Jayapura Meteorological Station. The data includes daily weather observations processed into monthly data, including rainfall parameters, temperature, humidity, direction, and wind speed. Mountainous areas have relatively more stable wind patterns than coastal areas, while ENSO and Indian Ocean Dipole (IOD) variability affect changes in wind circulation and water vapor distribution. These conditions are associated with decreased rainfall during El Niño and IOD+ phases and increased rainfall during La Niña and IOD- phases.